Marketing Strategy of Serai Wangi Dish Soap Produscts PT. Aroma Wangi Indonesia Pangkalpinang City - Dhaffa Nabila Sukanda; Eddy Jajang Jaya Atmaja; Evahelda Evahelda (Universitas Muhammadiyah Palembang, 2024)
This study aims to formulate alternative strategies and determine priority strategies in marketing fragrant lemongrass dishwashing soap products of PT. Aroma Wangi Indonesia in Pangkalpinang City. This research was conducted from April to July 2024 at PT Aroma Wangi Indonesia. The research method used is the case study method. The sampling method used was purposive sampling with a sample of 5 respondents. The analysis method uses qualitative descriptive and analysis (SWOT) and Quantitative (QSPM). The results showed that the IFE value was 3.04 and the EFE value was 3.33. Alternative strategies that can be applied in marketing citronella dish soap products PT. Aroma Wangi Indonesia in Pangkalpinang City is to improve brand image and product quality, but still maintain prices, develop and diversify citronella-based products, collaborate with modern markets, hotels, and the catering service sector and participate in training programs from government agencies, intensify marketing that is less than optimal through digital marketing and participate in MSME events periodically, create attractive product layout and explanation concepts, improve the suitability of products displayed on social media with marketed products such as providing customer testimonials of sales results, complete licensing and environmentally friendly logos on product packaging to build consumer confidence, and maximize operational management to increase sales profits. Based on the QSPM matrix, the top priority strategies to implement are establishing cooperation with modern markets, hotels, and the food service sector and participating in training programs from government agencies with a ∑TAS value of 6.90.